Phenotypic and molecular characteristics of CF patients carrying the I1234V mutation. (August 2020) - El Bar Aluma, Bat; Sarouk, Ifat; Senderowitz, Hanoch; Cohen-Cymberknoh, Malena; Khazanov, Netaly; Dagan, Adi; Bezalel, Yael; Ashkenazi, Moshe; Keler, Shlomit; Efrati, Ori
Abstract: Background: The Mutation I1234V is a CF causing mutation; however the mechanisms leading to loss of function are not fully understood. In this study, we aimed to characterize phenotypically individuals with the I1234V variant, and to gain a structural point of view of the mutant CFTR using computational studies. Methods: We conducted a retrospective descriptive study, reviewing the clinical records of 9 Israeli patients. The study was designed to include patients either homozygous or compound heterozygous for the I1234V mutation. For a comparison we analyzed clinical data of 12 patients homozygous for the F508del mutation. Computer models were constructed for I1234V, 1234-1239del and wild type CFTR. Results: Mean FEV1 was 73.8 ± 21% predicted with an average annual rate of decline of 1%. When compared to patients homozygous for F508del the mean annual values of FEV1% predicted during the 6 years of data collection ranged from 51 to 58 ± 22–30 in the F508del group versus 76–82 ± 14–19 in the I1234V group (p < 0.05). Structural models did not demonstrate noticeable differences between the three simulated constructs. Although the mutation resides in the NBD2, no interference with ATP binding was detected. Discussion: This study describes phenotypically patients carrying the I1234V mutation. Compared to patients homozygous for F508del, these patients present with more favorable outcome. Structural models show high similarity between the static and dynamics pictures obtained for both the mutated and the WT-CFTR; however this model does not explore the folding process and therefore may strengthen the notion of a misfolding mutation. Highlights: Although clinical data regarding this mutation is limited, the I1234V mutation is common among Arab-Muslim populations. The mechanisms leading to loss of function is not fully understood. This study implies by molecular dynamic simulation that the mutation may be a part of the class II mutation and results in CFTR misfolfing. Although patients present with abnormal sweat chloride results which indicates substantially low CFTR activity, as in patients homozygous for the 508 del mutation; phenotypically the disease is milder with more favorable outcome.